UJI validitas dan reliabilitas kuisoner Kepuasan konsumen Pengujian Sampel Lab. Terpadu FST UIN Sunan Kalijaga Yogyakarta - Sutriyono Sutriyono (UIN Sunan Kalijaga Yogyakarta, 2016)
This research aim to know level of validity and reliability kuisoner satisfaction of sample test consumer in Integrated Laboratory Science and Technology Faculty UIN Sunan Kalijaga. Valid and mainstay an instrument in this case quizoner sampling test hardly determines success in determining level of satisfaction of consumer matching with reality. Retrieval of data in this research by using quizoner, while data analysis applied is Correlation Test Pearson Product Moment and Alpha Cronbach's Test. Validity test indicates that valid of kuisoner satisfaction of integrated laboratory sampling test consumer which consist of tangibles ( X1), assurance ( X2), reliability ( X3), responsiveness ( X4), emphaty ( X5) can expressed valid, calculate r of all indikator/ variable to total score bigger than tables r ( 0,2458) with level significance 1%. Where highest valid there is at variable assurance ( X2) with correlation value reachs 0,887. While to testing reliability with level signifikasi 5% ( table r 0,1882) indicates that mainstay quizoner satisfaction of integrated laboratory sampling test consumer has level of high reliability with value Apha 0,825.